SISTEM INFORMASI PEMASARAN IKAN PADA PENJUAL IKAN SEGAR BERKAH BERBASIS APLIKASI ANDROID MOBILE DI KELURAHAN SEMPAJA BARAT KECAMATAN SAMARINDA UTARA KOTA SAMARINDA - Yoga Pratama, Agung; Abdusysyahid, Said; Gunawan, Bambang Indratno (2339-1324, 2024)
Fish Marketing System Information for Ikan Segar Berkah Seller Based Android Mobile Application in Sempaja West Village North Samarinda District Samarinda City (Supervised) by Dr. Ir. Said Abdusysyahid, M.Si and Dr. H. Bambang Indratno Gunawan, S.Pi., M.Si. This research aims to build an android mobile-based application for fresh fish sellers in the West Sempaja Subdistrict, North Samarinda District, Samarinda City to make it easier to manage shops, sales transactions, and in marketing fish for the system development method using the SDLC (System Development Life Cycle) method. This research method uses survey methods and data collection methods use survey methods. While the analysis and design of applications using several tools, namely Android Studio, Firebase, Figma, Data Flow Diagrams, and Flowcharts. In addition, unit testing uses the Black Box method to find out whether the application is running well. Based on the results of the BlackBox test, it can be concluded that the application that has been built can manage stores, manage financial transactions, and sell fish into an application. Keywords : Application, Android, Mobile, System Information